Effect of estradiol cypionate and amount of progesterone in the intravaginal device on synchronization of estrus, ovulation and on pregnancy rate in beef cows treated with FTAI based protocols - Uslenghi, Gastón (2014)
Three experiments were conducted to evaluate the effect of estradiol cypionate (ECP) andamount of progesterone in the intravaginal device (PID) on synchronization of estrus andovulation, follicular dynamics, luteal dynamics and function and on pregnancy rate in beefcows treated with fixed-time artificial insemination (FTAI) based protocols. In Experiment 1,we evaluated the synchronization of ovulation using 1 mg of ECP at PID removal (day 8 afterPID insertion) or 1 mg of estradiol benzoate (EB) 24 h later, in cows treated with 0.558 or 1 gof progesterone (P4). The final subgroups were: 0.558 g + ECP: n = 10; 0.558 g + EB: n = 11;1 g + ECP: n = 10; 1 g + EB: n = 10. Ovarian ultrasonic examinations were performed to detectthe dominant follicle and ovulation. There was no effect of treatments on the diameter ofdominant follicle at any time, and on the mean interval to estrus and to ovulation (P > 0.05);however, ECP treated cows had scattered distribution of estrus (P < 0.03) and ovulation(P < 0.03). In Experiment 2, cows received the following treatments: 0.558gP4 + ECP: n = 52;0.558gP4 + EB: n = 52; 1gP4 + ECP: n = 50; 1gP4 + EB: n = 52; and FTAI. Pregnancy rate did notdiffer (P > 0.05) between progesterone content (0.558 g: 52.9%, 55/104; 1 g: 56.9%, 58/102)but differed between estradiol esters (P < 0.05; ECP: 48.9%, 49/102; EB: 61.5%, 64/104).In Experiment 3, cows received: 0.558gP4 + ECP: n = 55; 0.558gP4 + EB: n = 53; 1gP4 + ECP:n = 54; 1gP4 + EB: n = 53; and FTAI. Pregnancy rate did not differ (P > 0.05) between proges-terone content (0.558 g: 48.1%, 52/108; 1 g: 53.3%, 57/107) and estradiol esters (ECP: 47.7%,52/109; EB: 53.8%, 57/106). In conclusion, ECP administration at device removal and proges-terone content of PID has no influence on the synchronization of estrus, follicular dynamics,luteal dynamics and function. However, ECP administration affected the synchronizationof ovulation and pregnancy rate in non-suckling beef cows, but did not affected pregnancyrate in suckling beef cows. Future studies should evaluate the distribution of ovulations insuckling Bos taurus beef cows.